Pakistan Development Update, April 2015 - World Bank (Washington, DC, 2015)
The Pakistani economy faced four major domestic shocks as of April 2015: (i) a political sit-in by opposition parties in Islamabad that lasted between August and December and raised significant political uncertainty; (ii) the September floods in Punjab that affected agricultural crops; (iii) the postponed sale of Oil and Gas Development Company Limited (OGDCL) equity shares in November that reduced its expected privatization proceeds and foreign direct inflows (FDI); and (iv) the terrorist attack in a school in Peshawar that heightened security concerns. However, supported by a favorable slump in international oil prices, and steady implementation of structural reforms by the government, the economy is improving. Preliminary data for the first half of FY15 show growth picking up, driven mainly by strong performance in the agriculture and services sectors. Despite the floods last year, growth improved in the cotton, wheat, and rice crops. The services sector was boosted by transport, storage, communications, finance, and insurance. On the demand side, growth continues to be driven by private consumption partly fuelled by high remittance inflows. Credit to the private sector continued to grow, but slightly less rapidly than last year: as a percentage of GDP, it fell to 13.4 percent in January 2015 compared with 14.1 percent in January 2014. Pakistan is on track to meet a fiscal deficit target of 4.8 percent of GDP in FY15. The newly elected government appears to be committed to fiscal discipline and has made fiscal consolidation the cornerstone of its economic program supported by the IMF, the World Bank and other donors. At present, Pakistan is facing three sources of risk: first is the prospect of an early reversal of the fall in oil prices. Second is the repeat of political events of the first half that keep FDI flows and private investment low; and also affects foreign reserves, privatization program and growth prospects. An uncertain political environment undermines investor confidence and depresses economic activity. Third is the continuation of a troubled domestic energy sector that continues to endure a long-due complex inheritance on its circular debt. Given past trends and the current growth rate, poverty is expected to continue to fall and shared prosperity to improve in this and the next fiscal year. However, a large mass of the population is clustered around the official poverty line, so that small improvements in household real consumption can translate into substantial movement in poverty in either direction.